Analisis Permasalahan Etika Pejabat Pemerintahan Dari Perspektif Administrasi Publik - Fitri Hayani; Indah Oktavia; Rindu Oktavia; Septa Adri Fania; Yulia Hanoselina; Rahmadhona Fitri Helmi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study analyzes the ethical problems of government officials from the perspective of public administration, which plays an important role in realizing good governance. This study uses a literature study approach by collecting data from journals, books, and relevant documents. The results of the study show that ethical violations, such as abuse of authority, corruption, collusion, and nepotism (CCN), are still frequent at various levels of government. The impact of this violation is a decrease in public trust and the quality of government services. The proposed solutions include strengthening regulations, strict sanctions, bureaucratic reform, and improving ethics education for public officials. This study emphasizes that the application of ethics in public administration is the key to increasing accountability, integrity, and transparency in public services.